2017
DOI: 10.1038/cddis.2017.389
|View full text |Cite
|
Sign up to set email alerts
|

Total tanshinones exhibits anti-inflammatory effects through blocking TLR4 dimerization via the MyD88 pathway

Abstract: Tanshinones belong to a group of lipophilic constituents of Salvia miltiorrhiza Bunge (Danshen), which is widely used in traditional Chinese medicine. A deluge of studies demonstrated that tanshinones exert anti-inflammatory effects, but the underlying mechanisms remain unclear to date. This study investigated the anti-inflammatory effects and mechanisms of total tanshinones (TTN). TTN suppressed the expression of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) and the secretion of TNF-α, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 45 publications
(53 reference statements)
2
41
0
Order By: Relevance
“…It is traditionally used in the treatment of cardiovascular and cerebrovascular diseases in China Shi et al, 2019;Sun et al, 2019). Modern pharmaceutical studies showed that tanshinone also possess antiangiogenic, antioxidant, antibacterial, anti-inflammatory, and antitumor activities (Wang et al, 2016;Gao et al, 2017;Zhou et al, 2017). According to the chemical structure, tanshinones could be classified into different types, out of which tanshinone IIA (Tan IIA), dihydrotanshinone (DT), tanshinone I (Tan I), and cryptotanshinone (CT) generally considered most important (Hao et al, 2016a;Shi et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…It is traditionally used in the treatment of cardiovascular and cerebrovascular diseases in China Shi et al, 2019;Sun et al, 2019). Modern pharmaceutical studies showed that tanshinone also possess antiangiogenic, antioxidant, antibacterial, anti-inflammatory, and antitumor activities (Wang et al, 2016;Gao et al, 2017;Zhou et al, 2017). According to the chemical structure, tanshinones could be classified into different types, out of which tanshinone IIA (Tan IIA), dihydrotanshinone (DT), tanshinone I (Tan I), and cryptotanshinone (CT) generally considered most important (Hao et al, 2016a;Shi et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a number of studies indicating the suppressive effect of different natural products (shinbaro3, curcumin, tanshinones, phloretin, xanthohumol, celastrol, garlic compounds etc.) on the different TLRs signaling (14,(23)(24)(25)(26). Additionally, several promising natural compounds (shinbaro3, curcumin, tanshinones) exert anti-inflammatory activities by suppressing TLR4/MyD88/NF-κB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages, the innate immune cells, play a predominant role in tissue inflammation response for eliminating invading pathogens ( Gao et al, 2017 ; Wu et al, 2017 ). Nevertheless, persistent or uncontrolled macrophage activation usually leads to the aberrant release of inflammatory cytokines and tissue damage ( Gao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages, the innate immune cells, play a predominant role in tissue inflammation response for eliminating invading pathogens ( Gao et al, 2017 ; Wu et al, 2017 ). Nevertheless, persistent or uncontrolled macrophage activation usually leads to the aberrant release of inflammatory cytokines and tissue damage ( Gao et al, 2017 ). In recent decades, considerable investigations have shown that macrophage activation and subsequent inflammatory response contribute to the pathogenesis of a variety of serious diseases, including, but not limited to the tumor, cardiovascular disease, neurodegenerative disorder, obesity, and diabetes ( Ku et al, 2016 ; Mondal et al, 2016 ; Reyes-Farias et al, 2016 ; Liou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%